Off‐pump coronary artery bypass grafting for patients with severely reduced ventricular function—A justified strategy?. Issue 1 (5th February 2021) - Neumann, Anneke; Serna‐Higuita, Lina; Detzel, Hendrik; Popov, Aron‐Frederik; Krüger, Tobias; Vöhringer, Luise; Schlensak, Christian
Abstract: Background and Aim: Low ejection fraction (EF) has been identified as a main risk factor for perioperative complications and mortality after coronary artery bypass grafting (CABG). The purpose of this study was to compare the efficacy and early as well as midterm outcomes of off‐pump CABG (OPCAB) and conventional CABG (ONCAB) surgery in patients with reduced EF. Methods: We performed a retrospective review of patient demographics, preoperative risk factors, operative and postoperative outcomes of patients with left ventricular EF (LV‐EF) ≤35%, who underwent CABG at our institution between January 2015 and December 2017. Propensity score and multivariate logistic regression analysis were used to compare risk adjusted outcomes between groups. Results: Overall, 111 consecutive CABG‐patients with LV‐EF ≤ 35% underwent either ONCAB (46 patients, 41.4%) or OPCAB surgery (65 patients, 58.6%). There was no difference in early mortality (5% vs. 7.5%, p = .64) between groups. After propensity score matching, OPCAB‐patients required significantly less re‐sternotomies for bleeding (20% vs. 2.5%, p = .03) and consequently received significantly less blood transfusions (57.5% vs. 32.5%, p = .03). Fewer OPCAB‐patients experienced low cardiac output syndrome (22.5% vs. 42.5%, p = .06) and suffered from postoperative delirium (22.5% vs. 42.5%, p = .06). There were no differences in completeness of revascularization between groups (median 1 (1.0–1.33; 1.0–1.33) OPCAB versus median 1 (1–1.33; 0.67–2) ONCAB, p = .95). Survival after 6 months, one year and three years was similar for ONCAB‐ and OPCAB‐patients (ONCAB 92.3%, 89.4%, and 89.4% vs. OPCAB 89.8%, 85.7%, and 82.1%; p = .403). More ONCAB‐patients needed a coronary re‐intervention during follow‐up (8.6% vs. 2.3%, p = .402). Conclusion: OPCAB‐surgery is a safe and effective option for patients with reduced EF. Furthermore, it does not come at the expense of less complete revascularization or increased coronary re‐intervention during early follow‐up.